Neuroconductor: an R platform for medical imaging analysis. (6th January 2018) - Muschelli, John; Gherman, Adrian; Fortin, Jean-Philippe; Avants, Brian; Whitcher, Brandon; Clayden, Jonathan D; Caffo, Brian S; Crainiceanu, Ciprian M
SUMMARY: Neuroconductor (https://neuroconductor.org ) is an open-source platform for rapid testing and dissemination of reproducible computational imaging software. The goals of the project are to: (i) provide a centralized repository of R software dedicated to image analysis, (ii) disseminate software updates quickly, (iii) train a large, diverse community of scientists using detailed tutorials and short courses, (iv) increase software quality via automatic and manual quality controls, and (v) promote reproducibility of image data analysis. Based on the programming language R (https://www.r-project.org/ ), Neuroconductor starts with 51 inter-operable packages that cover multiple areas of imaging including visualization, data processing and storage, and statistical inference. Neuroconductor accepts new R package submissions, which are subject to a formal review and continuous automated testing. We provide a description of the purpose of Neuroconductor and the user and developer experience.